Using electricity : switch it on - Pipe, Jim (New Delhi : S.Chand publishing, 2011)
An introduction to electricity and its uses, including key science vocabulary. Includes notes for parents and teachers. Suggested level: junior, primary.
Includes index.
Keywords: Readers Electricity